Land use change and carbon emissions of a transformation to timber cities - Mishra, Abhijeet; Humpenöder, Florian; Churkina, Galina; Reyer, Christopher P. O.; Beier, Felicitas; Bodirsky, Benjamin Leon; Schellnhuber, Hans Joachim; Lotze-Campen, Hermann; Popp, Alexander (Nature communications, 2022)
Using engineered wood for construction has been discussed for climate change mitigation. It remains unclear where and in which way the additional demand for wooden construction material shall be fulfilled. Here we assess the global and regional impacts of increased demand for engineered wood on land use and associated CO 2 emissions until 2100 using an open-source land system model. We show that if 90% of the new urban population would be housed in newly built urban mid-rise buildings with wooden constructions, 106 Gt of additional CO 2 could be saved by 2100. Forest plantations would need to expand by up to 149 Mha by 2100 and harvests from unprotected natural forests would increase. Our results indicate that expansion of timber plantations for wooden buildings is possible without major repercussions on agricultural production. Strong governance and careful planning are required to ensure a sustainable transition to timber cities even if frontier forests and biodiversity hotspots are protected. Wood used in construction stores carbon and reduces the emissions from steel and cement production. Transformation to timber cities while protecting forest and biodiversity is possible without significant increase in competition for land.